Utilization of maternal health care services and their determinants in Karnataka State, India. Issue 1 (June 2016) - Vidler, Marianne; Ramadurg, Umesh; Charantimath, Umesh; Katageri, Geetanjali; Karadiguddi, Chandrashekhar; Sawchuck, Diane; Qureshi, Rahat; Dharamsi, Shafik; Joshi, Anjali; von Dadelszen, Peter; Derman, Richard; Bellad, Mrutyunjaya; et al.
Abstract Background Karnataka State continues to have the highest rates of maternal mortality in south India at 144/100, 000 live births, but lower than the national estimates of 190–220/100, 000 live births. Various barriers exist to timely and appropriate utilization of services during pregnancy, childbirth and postpartum. This study aimed to describe the patterns and determinants of routine and emergency maternal health care utilization in rural Karnataka State, India. Methods This study was conducted in Karnataka in 2012–2013. Purposive sampling was used to convene twenty three focus groups and twelve individual interviews with community and health system representatives: Auxiliary Nurse Midwives and Staff Nurses, Accredited Social Health Activists, community leaders, male decision-makers, female decision-makers, women of reproductive age, medical officers, private health care providers, senior health administrators, District health officers, and obstetricians. Local researchers familiar with the setting and language conducted all focus groups and interviews, these researchers were not known to community participants. All discussions were audio recorded, transcribed, and translated to English for analysis. A thematic analysis approach was taken utilizing ana priori thematic framework as well as inductive identification of themes. Results Most women in the focus groups reported regular antenatal care attendance, for an average of four visits, and more often for high-risk pregnancies. Antenatal care was typically delivered at the periphery by non-specialised providers. Participants reported that sought was care women experienced danger signs of complications. Postpartum care was reportedly rare, and mainly sought for the purpose of neonatal care. Factors that influenced women's care-seeking included their limited autonomy, poor access to and funding for transport for non-emergent conditions, perceived poor quality of health care facilities, and the costs of care. Conclusions Rural south Indian communities reported regular use of health care services during pregnancy and for delivery. Uptake of maternity care services was attributed to new government programmes and increased availability of maternity services; nevertheless, some women delayed disclosure of pregnancy and first antenatal visit. Community-based initiatives should be enhanced to encourage early disclosure of pregnancies and to provide the community information regarding the importance of facility-based care. Health facility infrastructure in rural Karnataka should also be enhanced to ensure a consistent power supply and improved cleanliness on the wards. Trial registration NCT01911494